(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
With the increasing need for more better way to consume a service during the Covid-19 pandemic, as well as the need of more flexible way to register for the beds in the hospitals, this paper introduces a Web Application which is shaped to provide easy access to book a bed in the hospital for the needy. This framework connects the consumer to an online interface to register themselves and book a bed on their name and hospitals to register themselves and provide their details providing a time efficient way to ease the efforts. It securely maintains the data of users in a database working behind.